HUBUNGAN DEPRESI DENGAN LAMA MASA TAHANAN NARAPIDANA DI RUMAH TAHANAN NEGARA KELAS IIA MALENDENG MANADO - Tinneke A. Tololiu; Siti Hardiyanty Makalalag (Jurnal Ilmiah Perawat Manado (Juiperdo), 2015)
Depression is a very deepened sorrow feeling seriously that happened on prisoner as a result from convicted criminal. This sorrow feeling caused prisoner experienced it life means, hopelessness feel and have not motivation and avoided by families or the other. Convicted prisons action in the Country House Detention II A class Malendeng of Manado on 2012 year as amount as 3390 prisoner. By the mounth January until to February 2013 year as much as 529 prisoner and 50 persons (9,5%), Consisted to robbing case. Aims this research is to identification of relationship between depression with long terms periode of prisoner detention. Research design is analytic description with cross sectional study approach to describe and identification of there is relationship between depression with long term periode prisoner detention. Population is all of prisoner with robbing case. Sample obtained technic is total sampling that meet a demand inclusive criteria and exclusive criteria as a mount 50 persons. Data taking using with questioner by The Burns Depression. Data analysis result founded that the prisoner ages as muchly between 15-30 years amount 44% with men sexual amount 84% and education level SMP as much 50%. Detention long terms periode between 1-2 years as amount 44%. Most of prisoner experienced moderate depression as much 56%, severe depression 16%, and most of a bit mild depression as much 14 persons (28%). Statistic test result using chi-square, founded that pValue= 0,000<α 0,05, that means there was significantly relationship between depression with prisoner detention long term periode in Country House Detention Malendeng II A Class of Manado